Modulating effect of HERV-W ENV on peripheral blood monocytes in patients with different types of multiple sclerosis - O. M. Koliada; N. I. Vdovichenko; T. I. Koliada; O. V. Tupotilov (Zaporozhye State Medical University, 2022)
The aim of the study was to determine the effect of the HERV-W ENV glycoprotein on the functional and metabolic characteristics of intact and stimulated peripheral blood monocytes, depending on the type of multiple sclerosis (MS), which can contribute to our understanding of their pathogenetic role in the development of neurological disorders and to design of novel therapeutic agents. Materials and methods. To determine the reserve capacity index (Rci) of cytokine production, HERV-W ENV glycoprotein, E. coli lipopolysaccharide (LPS) or ssRNA40/LyoVec were added to the monocyte-enriched cell suspension as agonists of TLR4 and TLR7/8. The study also included the evaluation of arginase activity in cell lysates of the monocyte fraction. The study involved 37 patients with relapsing-remitting type and 19 patients with progressive type of MS. The control group included 32 healthy individuals. Results. In patients with MS of both groups, the reserve capacity of monocytes to produce IL-1β was lower than in healthy individuals, while the reserve capacity to produce TNF-α and IL-10 was almost twice as high as in the control group. This index for IL-1RA in monocytes obtained from the group with progressive MS and stimulated with HERV-W ENV was 2 times lower than the control; thus increased IL-1β values provoke chronic inflammation. The highest arginase activity in patients with relapsing-remitting MS was observed when monocytes were cultured with HERV-W ENV and LPS. In patients with progressive MS, during the cultivation of monocytes with LPS, arginase activity was significantly reduced relative to the control. Conclusions. The results obtained indicate functional and metabolic changes in peripheral blood monocytes upon stimulation with TLR4 and TLR7/8, which may be associated with the disease course. In progressive MS, stimulation with HERV-W ENV leads to an imbalance of pro-inflammatory and regulatory cytokines, contributing to a chronic inflammation and, as a consequence, to a more severe course of the disease.